Mechanically enhanced graphene oxide/carboxymethyl cellulose nanofibril composite fiber as a scalable adsorbent for heavy metal removal - Yu, Hayoung; Hong, Hye-Jin; Kim, Seung Min; Ko, Heung Cho; Jeong, Hyeon Su (Pergamon Press Ltd., 2020)
Recently, graphene oxide(GO) has gained much attention for heavy metal removal due to its high surface area and lots of functional groups on the surface. However, GO itself in powder form is far away from practical adsorbents because it remains dispersed in liquid phase which causes difficulty in the separation from effluent. In this study, GO/carboxymethyl cellulose nanofibril (CMCNF) composite fiber(CF) is developed as an efficient and durable adsorbent. Cross-linked GO/CMCNF CF was continuously produced by employing Fe3+ ion as a coagulant during a typical wet-spinning process. Based on multiple interactions such as ionic bonding and electrostatic interactions between Fe3+ and carboxyl group on CMCNF, the CF exhibits enhanced mechanical property than pure GO fiber. GO/CMCNF-Fe3+ CF showed efficient lead (Pb2+) uptake with successful adsorbent recovery, which indicates durable and cost-competitive fiber type adsorbent for heavy metal ions.